Access of patients with breast and lung cancer to chemotherapy treatment in public and private hospitals in the city of Buenos Aires - Recondo, Gonzalo (2019)
Objectives: Describe the time elapsed from the diagnosis to treatment with chemotherapy for patients with breast and lung cancer at public and private hospitals in Buenos Aires. Design: Retrospective cohort study. Setting: Three public and three private academic hospitals in Buenos Aires. Participants: Patients with breast (n = 168) or lung cancer (n = 100) diagnosis treated with chemotherapy. Main outcomes measures: Clinical and sociodemographic data were collected in a stratified sample. We used the Kaplan–Meier estimator to analyse the time elapsed and the log rank test to compare both groups Results: For breast cancer patients, median time elapsed between diagnosis and treatment with chemotherapy was 76 days (95% CI: 64–86) in public and 60 days (95% CI: 52–65) in private hospitals (P = 0.0001). For adjuvant and neoadjuvant treatments, median time was 130 (95% CI: 109–159) versus 64 (95% CI: 56–73) days (P < 0.0001) and 57 days (95% CI: 49–75) versus 26 (95% CI: 16–41) days, respectively (P = 0.0002). There were no significant differences in the time from first consultation to diagnosis. In patients with lung cancer, median time from diagnosis to treatment was 71 days (95% CI: 60–83) in public hospitals and 31 days (95% CI: 24–39) in private hospitals (P = 0.0002). In the metastatic setting, median time to treatment was 63 days (95% CI: 45–83) in public and 33 (95% CI: 26–44) days in private hospitals (P = 0.005). Conclusions: There are significant disparity in the access to treatment with chemotherapy for patients in Buenos Aires, Argentina.